Investigating the Use of Project-Based Learning Using Animated Video Media in English Learning, Writing Descriptive Text at Vocational High School Students - Naufal Syafiqri (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
This study examines the implementation of Project-Based Learning using animated videos in teaching descriptive writing to vocational high school students and explores students' experiences with this integrated approach. Using a case study design, data were collected through observations and interviews with teachers and students. The results of the study indicate that teachers successfully implemented a structured project-based learning approach, beginning with an explanation of the material, followed by the screening of animated videos, group discussions for text writing (planning, drafting, editing, and final presentation), and reflection. The animated video "Get to know more about Borobudur Temple" served as an engaging and educational tool. Students' overall responses were positive across all cognitive, affective, and conative domains. Cognitively, students demonstrated better understanding of descriptive text structure and vocabulary, as well as improved critical thinking skills. Affectively, they reported increased enjoyment, motivation, and preference for this interactive learning method. In terms of conative skills, students actively participated in group work, showed improved writing skills, and, despite minor initial confusion, completed the project creation process. This study concludes that integrating project-based learning with animated videos is a highly effective and engaging pedagogical strategy for increasing descriptive writing skills in English and creating positive learning experiences in a vocational high school environment.